(untitled) (Jurnal Pembangunan Sosial, 2011)
Nowadays the number of older people entering Rumah Seri Kenangan is keep increasing. This study focuses the discussion on the commitment of older people in religious activities at Rumah Seri Kenangan Cheras. From 78 Muslim elderly at Rumah Seri Kenangan Cheras, a total of 36 older people were chosen as sample through simple random sampling. Data were gathered through questionnaire. The study points out that the level of commitment of the older people at Rumah Seri Kenangan Cheras in religious activities are moderate, but their level of religious knowledge is high. This study also shows that there is a positive and significant relationship between the level of religious knowledge with the commitment of the older people in religious activities. On the whole, the commitments of the older people in religious activities are associated with their level of religious knowledge. However, the high level of religious knowledge is not the main factor in encouraging them to give commitment in religious activities.